Global Analysis of 24 Rovibrational Bands of the Octad of the 76GeH4 Molecule; Russian Physics Journal; Vol. 63, iss. 11 - Raspopova N. I. Natalya Ivanovna; Gromova O. V. Olga Vasilievna; Bekhtereva E. S. Elena Sergeevna; Koshelev M. A. Maksim Aleksandrovich; Sennikov P. G. Petr Gennadjevich (2021, 2021)
Title screen